Unraveling the contribution of ectoenzymes to myeloma life and survival in the bone marrow niche. (21st July 2014) - Quarona, Valeria; Ferri, Valentina; Chillemi, Antonella; Bolzoni, Marina; Mancini, Cristina; Zaccarello, Gianluca; Roato, Ilaria; Morandi, Fabio; Marimpietri, Danilo; Faccani, Giuliano; Martella, Eugenia; Pistoia, Vito; et al.
Abstract : The bone marrow provides a protected environment for generating a vast array of cell types. Bones are thus a dynamic source of structural components and soluble factors used either locally or at a distance from their site of production. We discuss the role of ectoenzymes in the bone niche where human myeloma grows. Selected ectoenzymes have been tested for their ability to promote production of substrates involved in signaling, synthesis of growth factors and hormones, and modulation of the immune response. Because of the difficulty of simultaneously tracking all these activities, we narrow our focus to events potentially influencing synthesis of adenosine (ADO), an important regulator of multiple biological functions, including local immunological tolerance. Our working hypothesis, to be discussed and partially tested herein, is that CD38, and likely BST1/CD157—both NAD + ‐consuming enzymes, are active in the myeloma niche and lead a discontinuous chain of ectoenzymes whose final products are exploited by the neoplastic plasma cell as part of its local survival strategy. Coadjuvant ectoenzymes include PC‐1/CD203a, CD39, and CD73, which control the production of ADO. Results discussed here and from ongoing experiments indicate that the myeloma niche hosts the canonical, as well as alternative, pathways of ADO generation. Other possibilities are presented and discussed.